UANG PANAI DALAM PERSPEKTIF HUKUM ISLAM: DAMPAK TERHADAP KESIAPAN FINANSIAL PASANGAN MUDA - Rafidah; Ahyat Habibi (LPPM STAI Muhammadiyah Probolinggo, 2026)
Indonesia is a nation with rich cultural diversity, where customs continue to influence social and family life. One tradition is uang panai among the Bugis people of South Sulawesi, a sum of money given by the groom to the bride’s family as a symbol of respect and sincerity in marriage. In modern society, this practice is often influenced by social competition, affecting the economic readiness of young couple. This study aims to analyze the economic impact of uang panai on financial readiness, examine it from the perspective of Islamic law, and formulate solutions so the tradition can be preserved without economic burden. This research uses a descriptive qualitative approach based on literature and social analysis. The findings show that uang panai significantly affects financial readiness by encouraging discipline and planning. However, it can become a source of pressure when economic capacity is ignored. Therefore, balance between tradition and financial ability is necessary. From an Islamic law perspective, uang panai is permissible as long as it does not replace the mahar, does not cause harm, and upholds honor. With proportional application and mutual agreement between families, uang panai can remain a valid custom consistent with justice and ease in Islamic law.